The biological and psychological trend in explaining violent and criminal behavior in society: critical reading - Amina Aguenin (Social Empowerment Journal, 2022)
This study aims to reveal some biological and psychological explanations for the behavior of violence and crime in society. Biological explanations provided a new perspective in explaining the phenomenon, relying on the biological characteristics of the individual and his physical characteristics in the appearance of violent and criminal behavior. However, the latter have been severely criticized, including the fact that it is difficult to say that human beings are born criminals by nature, and the evidence is that there are bad people who have the same biological characteristics as criminals, and these explanations lack the soundness of the scientific method of presentation. Psychological interpretations of human behavior occupy a distinctive place in the social sciences, especially in interpreting violent behavior and crime. However, they have also been subjected to various criticisms, especially the theory of psychoanalysis, which researchers believe that there is no clear scientific evidence for a relationship between the internal self-state of the mind and violent behavior.These interpretations neglect social and cultural factors in their analysis, especially since human behavior is primarily the result of social experiences and is not determined by instincts or tendencies, as these theories claim.